Pengaruh Motivasi Belajar, Self Efficacy, dan Self Regulated Learning Terhadap Hasil Belajar Matematika - Meiliati, Rafika; Darwis, Muhammad; Asdar (Issues in Mathematics Education (IMED), 2018)
This research is an expo facto research which airms to find out the influence of Learning Motivation, Self Efficacy, Self Regulated Learning to Student Learning Outcones of Mathematics GradeXI IPA Senior High School in Enrekang Regency. The population in this research is the student of grade XI IPA Senior High School in Enrekang Regency academic. The sample of this research is 120 student which is taken by using stratified random proportional sampling technique. The data were collected by using four instruments. Data were analyzed by using descriptive statistica and path analysis. Data management is done with the help of SPSS statistical program. The result of the shows that: (1) student’s learning motivation is in low category, (2) self efficacy and self regulated learning of student is in high category, (3) result of studemt’s mathematics learning is in medium category, (5) student’s learning motivation directly have a significant positive effect to self regulated learning, (6) self efficacy of student directly have a significant positive effect on self regulated learning, (7) student’s learning motivation directly has no significant positive effect on result, (8) self efficacy of student directly have a significant negative effect on mathematics learning outcomes, (9) self regulated learning student directly have a significant positive effect on mathematics learning.